2004
DOI: 10.1007/s10735-004-2341-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the proliferation-associated nuclear protein MIB-1 and its relationship with microvascular density in bone marrow biopsies of patients with myelodysplastic syndromes

Abstract: The myelodysplastic syndromes (MDS) are a group of disorders characterized by dysplastic hemopoiesis and an increased risk of leukemic transformation. The process of angiogenesis has been implicated in the pathogenesis and evolution of MDS. In this study the proliferative activity and extent of angiogenesis was examined in bone marrow samples from 54 patients with MDS in relation to clinicopathologic features. Cellular proliferation and microvascular density (MVD) were examined immunohistochemically, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Our observations are in agreement with the published literature that indicates overexpression of p53 and Ki-67 in MDS/AML [5-7, 10, 16]; however, the close resemblance in overexpression of these markers between IBMFS and MDS/AML has not been reported previously. Similarities in the rate of overexpression of p53 and Ki-67 between IBMFS and MDS/AML may suggest a common cell cycle deregulation mechanism that is responsible for the preleukemic and leukemic processes in these marrow disorders.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observations are in agreement with the published literature that indicates overexpression of p53 and Ki-67 in MDS/AML [5-7, 10, 16]; however, the close resemblance in overexpression of these markers between IBMFS and MDS/AML has not been reported previously. Similarities in the rate of overexpression of p53 and Ki-67 between IBMFS and MDS/AML may suggest a common cell cycle deregulation mechanism that is responsible for the preleukemic and leukemic processes in these marrow disorders.…”
Section: Discussionsupporting
confidence: 93%
“…Overexpression of p53 was also observed in low grade MDS (refractory anemia [RA]) when compared with acquired aplastic anemia [8], and in a proportion of AML and MDS marrows [9]. While some studies noted that the expression of Ki-67 was higher in high risk than low risk MDS, and in MDS than in normal controls [10], others found no difference in the expression of Ki-67 mRNA between AML, ALL and normal controls [11]. Survivin expression was increased in more than half of over 100 bone marrow aspirates from patients treated for de novo AML, while most of the remaining samples lacked any expression [12]; in another study, survivin expression was higher in the marrow of MDS and MDS-derived leukemia than normal controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferative index of advanced MDS is uncertain, with some studies showing a decreased proliferative rate and others an increased proliferative rate, compared with early MDS. [52][53][54] Our data support a defect in regulation of the cell cycle in advanced MDS. The downregulation of several pathways involving the cell cycle in AML, including cell cycle regulation by BRCA1 and CDC25, has also recently been shown.…”
Section: Deregulated Pathways In Myelodysplastic Syndromes a Pellagatsupporting
confidence: 71%
“…Likewise, Wimazal, et al found increased MVD and elevated levels of VEGF in the bone marrows of patients with CMML; immature myeloid cells were the source of VEGF [68]. Alexandrakis et al further confirmed the importance of angiogenesis in CMML by demonstrating increased MVD and increased levels of angiogenin and interleukin 6 in patients with CMML [69, 70]. Finally, Bellamy, et al proposed an autocrine function of VEGF, demonstrating that some patients’ CMML cells expressed cytoplasmic VEGF as well as the membranous VEGF receptors Flt-1 and KDR.…”
Section: Biology and Pathophysiologymentioning
confidence: 99%